담양지역 연합판매사업 컨설팅 보고서 - 황의식 (한국농촌경제연구원, 2005)
This study aims to advise the marketing structure and strategies in common of the cooperatives in Damyang county. The current situation in the retail market such as increased market concentration of the super-center format is risk factor to cooperative marketing in production sites. The change of agricultural marketing environment leads to innovation in agricultural produce shippers and needs new adaptation of the agricultural cooperatives. The role of agricultural cooperative which is charge of marketing in agricultural producing district is very important. A suggested main direction is how to establish the cooperative marketing agency in common. In damyang county, small scale farmers' group in pooling is well developed. So, it is important of the related agents to share the vision of the market-oriented marketing strategies. To improve cooperation in strawberry marketing, pooling type will be converted point pooling schemes. Researchers: Hwang Eui-Sik, Park Jun-Gi, Moon Han-Pil E-mail address: eshwang@krei.re.kr